Sources of shallow natural gases in the Longgang marine gas field, NE Sichuan Basin: an example from the water conveyance tunnel - Shilin Wang; Xiangqian Guo; Peidong Su; Long Li; Mohamed S. Ahmed; Xiaojin Chu; Xiangbing Zhang; Thomas Gentzis; Ahmed Mansour; Ahmed Mansour (Frontiers in Earth Science)
With the advancement of the Tingzikou Irrigation Area Water Diversion Project, the issue of harmful shallow underground gases in the tunnel has become increasingly prominent. Identifying the causes, sources, and migration processes of these harmful gases is crucial to prevent possible catastrophic impacts and mitigation during tunnel construction. Here, we apply an integrated approach of carbon isotope composition to analyze the geochemical characteristics of shallow natural gas components from a high-gas water diversion tunnel in the Tingzikou Irrigati Area. Results are integrated and compared with data from the Sichuan Basin fault system and isotopic values from different strata to provide further evidence of the source of shallow natural gas in the area. The geochemical characteristics of the gas samples reveal that the methane content is the most abundant, and constitutes as high as 45.16%, while carbon oxides are in the range of 0.02%–0.1%. Heavier hydrocarbons (C2+) account for 2.27%, and the dryness coefficient is 0.96. These major components indicate the presence of wet gas with relatively low thermal maturity. The alkane gases exhibit a normal carbon sequence, with δ13C1 values less than −25‰, indicating that the gas originates from oil-type organic. The carbon dioxide is classified as Type II inorganic gas, and the hydrogen sulfide is attributed to thermochemical sulfate reduction origin. In the tunnel area, δ13C2 ranges from −29.53‰ to −28.11‰, with an average of −28.80‰, which are similar to the ethane isotope values of the J1l and J1m strata in the central Sichuan Basin, but heavier than those of the J1dn, J1d, and T2l strata, and significantly different from T3x. This reveals that the shallow natural gas originates from the shallow oil and gas source rock layers of the Ziliujing Formation at the Ziliujing anticline, making it a “self-generated and self-stored” gas.